Case Report of Esophageal Food Impaction in Partially Edentulous Patient - Diflayzer, Diflayzer (Majalah Kedokteran Andalas, 2025)
Introduction: Esophageal food impactionis a medical ailment characterised by the obstruction of the oesophagus due to food becoming stuck. Loss of teeth can lead to food impaction, which lowers the ability to chew and create a bolus. This can cause bigger food particles that interfere with swallowing. Objective: Understanding diagnosis dan management of Esophageal Food Impaction in which partially Edentulous as risk factor.Â  Case Report: A 60-year-old man came with complaints of having difficulty in swallowing since 3 days before admission. There was history of feeling something stuck in his throat after swallowing a chunk of meat. Oral cavity examination revealed missing 21 of teeth. There was standing secretion in pyriform sinus. The patient was managed with diagnostic and therapeutic esophagoscopy with diagnosis of impaction of "meat" food in the esophagus. A chunk of meat was removed at the level of 18 cm away from upper incisor. After removal, difficulty of swallowing was improved. Conclusion: Food bolus impaction â€œmeatâ€ can be successfully removed using rigid esophagoscopy without any complications. There was significant improvement in symptoms after removal of food impaction. Loss of teeth is a risk factor for food impaction in this case.Â